POPULATION RISK FACTORS FOR THE DEVELOPMENT OF EYE ILLNESSES AMONG CHILDREN - L.V. Nefedovskaya; Zh.V. Gudinova; A.A. Modestov ("Paediatrician" Publishers LLC, 2007)
The article highlights the research findings, describing analysis of the impact caused by the population risk factors upon the formation of the eye illnesses among children. The regression analysis of the above said factors on their basis was used to build the graphic regression models for the development of preventive actions. Key words: children, eye illnesses, risk factors.